Early clinical experience with resorbable poly-5D/95L-lactide (PLA95) plate system for treating distal radius fractures - Ing-Lin Chang; Jen-Chang Yang; Sheng-Yang Lee; Li-Fen Wang; Hsin-Tai Hu; Sung-Yu Yang; Hwang-Chi Lin (Elsevier, 2013)
Background/purpose: Distal radius fractures are amongst the most common musculoskeletal bone injuries treated in emergency departments. The objective of this study was to evaluate the functional and radiologic outcomes of treating distal radius fractures with a resorbable volar polymeric implant system. Materials and methods: We applied the volar poly-5D/95L-lactide (PLA95) plate/screw system (Bonamates, BioTech One, New Taipei City, Taiwan) for intraosseous fixation after open reduction of distally displaced radius fracture in four patients (three males and one female, ages range: 7-67 years). Another four patients [three females and one male, ages 68-70 (68.8 ± 1.0)] were treated with 3.5-mm metal volar T locking plates (Synthes, Paoli, PA, USA) as the control group. The minimum follow-up period was longer than 2.5 months for all cases. Results: At final functional and radiologic assessment, all of the distal radius fracture sites were united and one patient achieved excellent results, two patients had good results, and one had a fair result. All patient outcomes were satisfactory, and no major material-related infections or allergies were found. Conclusion: Within the limitations of this early clinical experiment, we conclude that the volar PLA95 copolymer plate/screw system can be used to treat distal radial fractures.